Comprehensive Optimization of Air Quality in Kitchen Based on Auxiliary Evaluation Indicators - Hai Huang; Shunyu Zhang; Xiangrui Zhao; Zhenlei Chen (Applied Sciences)
Traditional single-scale indoor air quality (IAQ) evaluation methods often fail to meet the demands of modern, personalized kitchens. To address this limitation, we propose a comprehensive IAQ index, integrating experimental data and simulation results. The index incorporates four key IAQ auxiliary evaluation indicators: air distribution performance index (ADPI), predicted mean vote (PMV), cooking oil fume particulates (COFP), and CO2 concentration. We developed a kitchen model and used the comprehensive IAQ index to benchmark simulation results against experimental tests. Optimal kitchen air quality occurred at a supply air angle of 90° and airflow velocity of 2.268 m3/min, reducing air pollution impact by 29.50%. This configuration enhanced thermal comfort while reducing secondary COFP accumulation in the breathing zone by 22%. The 29.50% Q-index reduction corresponded to a 24% decrease in peak CO2 exposure (638 ppm, clean-air level) and 22% lower COFP in breathing zones, mitigating health risks. Optimized airflow (2.268 m3/min) avoided excessive ventilation, reducing energy waste and achieving balanced IAQ-energy efficiency.